Do Ethical Judgments Depend on the Type of Response Scale? Comparing Acceptability versus Unacceptability Judgments in the Case of Life-Ending Procedures - Etienne Mullet; Paul C. Sorum; Astrid Lhermitte; Charlène González; María Teresa Muñoz Sastre (Psicológica, 2010)
Using Functional Measurement (Anderson, 2008), Frileux, Lelièvre, Muñoz Sastre, Mullet, and Sorum (2003) examined the joint impact of several key factors on lay people's judgments of the acceptability of physicians' interventions to end patients' lives. The level of acceptability was high, and the information integration rule that best described the participants' judgments was Acceptability = Patient's Request + Patient's Age + Residual Suffering + Incurability. Critics suggested, however, that acceptability was high because the ethical problem was framed in terms of acceptability (Murphy, 2007). Presenting participants with acceptability scales may have caused the life-ending procedure to be represented in participants' mind as basically "acceptable". By contrast, presenting participants with unacceptability scales might cause the procedure to be represented as basically "unacceptable". In the present study, therefore, we directly compared lay people's judgments of the acceptability of life-ending procedures under two opposite conditions - an acceptability condition, and an unacceptability condition. The life-ending procedure did not appear as more acceptable to participants responding in terms of acceptability than to those responding in terms of unacceptability. In addition, the impacts of the factors describing the end-of-life situations were not affected by the type of judgment scale that was used. Functional Measurement seems to be resistant to goal-framing effects; the findings that have been observed using acceptability scales can be considered as robust.